Peran Lembaga Keuangan Non Bank Dalam Memberikan Keadilan Distributif Bagi Nasabah - Irpan Suriadiata (LPPM Universitas Ekasakti Padang, 2024)
This research was conducted with the objectives: 1) To determine the role of non-bank financial institutions in providing distributive justice for customers. 2) To determine factors for improving non-bank financial institutions in providing distributive justice for customers. The type of research used in this research is normative legal research using statutory and conceptual approaches. The results of this research show that: 1) The role of non-bank institutions in providing distributive justice for customers, namely collecting funds; channeling funds, asset transfer, liquidity, income allocation and transactions. 2) Factors increasing non-bank financial institutions in providing distributive justice for customers, namely the large increase in the income of middle class families and individuals. with sufficient income, especially those in the middle class, have a certain portion of their income to save each year. Apart from that, the fact of increasing non-bank financial institutions is also dominated by the large denominations of financial instruments, which makes it difficult for small savers to gain access.